Gene Regulation by the transcription factor ZEB1 in Glioblastoma Multiforme - Rosmaninho, Pedro (2019)
Glioblastoma Multiforme (GBM) is the most prevalent type of glioma, bearing the highest incidence rate of brain and Central Nervous System (CNS) malignant tumors and the lowest survival rate. GBMs distinguish themselves from lower grade glial tumors by the presence of certain hallmark histological features such as the presence of central necrosis in the tumor mass, marginal proliferation of endothelial cells and the presence of palisading cells around the area of necrosis. Several hallmark features contribute to the poor responsiveness that GBM tumors have to treatment including their high inter- and intratumoral heterogeneity at a phenotypic, cellular, genetic and epigenetic level. Most importantly, the existence of cancer stem cell (CSC) populations within GBM tumors is crucial for driving invasive tumor growth due to their potential to proliferate in vascular conditions, while becoming highly invasive in hypoxic conditions. Moreover, the ability of GBM CSCs to infiltrate surrounding brain parenchyma means that even the smallest number of such cells left after surgery will cause tumor recurrence.(...)